Ionic-Liquid-Supported 1,3-Dimethylimidazolidin-2-one: Application as a Reusable Halogenation Reagent - Koguchi, Shinichi; Shibuya, Yuga; Igarashi, Yusuke; Takemura, Haruka (Synlett, 2019)
We describe the synthesis of ionic-liquid-supported 1,3-dimethylimidazolidin-2-one, together with the halogenation of alcohols in a reaction system in which this reagent is combined with oxalyl chloride. A new method was established that does not require additives such as bases, and which permits the ready isolation and purification of the product. Good conversions were obtained, and good reusability of the reagent was observed.
Keywords: ionic liquid; chlorination; alcohols; dimethylimidazolidinone; supported reagent